The Influence of Risk Perception, Smoking Fatwa Knowledge, and Smoking Behavior on the Intention to Quit Smoking in Adolescents - Ayuning Tyas; Retnaningsih Retnaningsih (Journal of Consumer Sciences, 2025)
Background: The percentage of adolescent smokers is increasing; however, survey results indicate that many adolescent smokers express a desire to quit.